Profiling non-coding RNA expression in cerebrospinal fluid of amyotrophic lateral sclerosis patients. (31st December 2022) - Joilin, Greig; Gray, Elizabeth; Thompson, Alexander G.; Talbot, Kevin; Leigh, P. Nigel; Newbury, Sarah F.; Turner, Martin R.; Hafezparast, Majid
Abstract: Introduction: Objective biomarkers for the fatal neurodegenerative disease amyotrophic lateral sclerosis or motor neuron disease (ALS/MND) are critical for diagnosis, drug development, clinical trials, and insight into disease pathology. Key candidates for biomarkers present in biofluids include non-coding RNA (ncRNA) transcripts including microRNA, piwi-interacting RNA and transfer RNA. To determine if the central nervous system was the source of the dysregulated ncRNA biomarkers we previously observed in serum, we sought to identify dysregulated ncRNA candidates in cerebrospinal fluid (CSF) which may provide new insight into the disease pathology. Methods and materials: Small RNA sequencing (RNA-seq) was undertaken on CSF samples from healthy controls ( n  = 18), disease mimics ( n  = 8), and ALS patients ( n  = 40) in our Oxford Study for Biomarkers of ALS cohort, with RT-qPCR used to confirm their dysregulation. Results: We found a range of ncRNA that were dysregulated in the RNA-seq screen, but these failed to be validated or detected in some cases using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Additionally, our previously identified serum ncRNA biomarker showed no change in CSF or correlation to serum. Conclusions: This study suggests the CSF may not be the source of dysregulated ncRNA in the serum and highlights the difficulty in identifying ncRNA in CSF as biomarkers for ALS. KEY MESSAGES: In this current study, we investigated the expression of non-coding RNA transcripts in the cerebrospinal fluid of ALS patients compared to healthy controls. RNA-seq identified dysregulated non-coding RNA transcripts, but these were not validated with RT-qPCR. We conclude that cerebrospinal fluid is not a suitable source of diagnostic biomarkers.